Albumin infusion in patients undergoing large-volume paracentesis: A meta-analysis of randomized trials - Bernardi, Mauro; Caraceni, Paolo; Navickis, Roberta J.; Wilkes, Mahlon M. (Hepatology (Baltimore, Md.), 2012)
Albumin infusion reduces the incidence of postparacentesis circulatory dysfunction among patients with cirrhosis and tense ascites, as compared with no treatment. Treatment alternatives to albumin, such as artificial colloids and vasoconstrictors, have been widely investigated. The aim of this meta‐analysis was to determine whether morbidity and mortality differ between patients receiving albumin versus alternative treatments. The meta‐analysis included randomized trials evaluating albumin infusion in patients with tense ascites. Primary endpoints were postparacentesis circulatory dysfunction, hyponatremia, and mortality. Eligible trials were sought by multiple methods, including computer searches of bibliographic and databases and the Cochrane Library. Results were quantitatively combined under a fixed‐effects model. Seventeen trials with 1,225 total patients were included. There was no evidence of heterogeneity or publication bias. Compared with alternative treatments, albumin reduced the incidence of postparacentesis circulatory dysfunction (odds ratio [OR], 0.39; 95% confidence interval [CI], 0.27‐0.55). Significant reductions in that complication by albumin were also shown in subgroup analyses versus each of the other volume expanders tested (e.g., dextran, gelatin, hydroxyethyl starch, and hypertonic saline). The occurrence of hyponatremia was also decreased by albumin, compared with alternative treatments (OR, 0.58; 95% CI, 0.39‐0.87). In addition, mortality was lower in patients receiving albumin than alternative treatments (OR, 0.64; 95% CI, 0.41‐0.98). Conclusions: This meta‐analysis provides evidence that albumin reduces morbidity and mortality among patients with tense ascites undergoing large‐volume paracentesis, as compared with alternative treatments investigated thus far. (HEPATOLOGY 2012)